2020
DOI: 10.1097/aud.0000000000000839
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Classification of Hearing Health Seeking in Adults Aged Over 50 Years in England

Abstract: Objectives: Approximately 10 to 35% of people with a hearing impairment own a hearing aid. The present study aims to identify barriers to obtaining a hearing aid and inform future interventions by examining the biopsychosocial characteristics of adults aged 50+ according to 7 categories: (i) Did not report hearing difficulties, (ii) Reported hearing difficulties, (iii) Told a healthcare professional about experiencing hearing difficulties, (iv) Referred for a hearing assessment, (v) Offered a hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 72 publications
4
53
2
Order By: Relevance
“…Overall, our findings in a large and recent clinical sample of older adults converge with the existent literature, showing self-reported hearing difficulties, audiometric hearing loss, and age are some of the strongest predictors of hearing aid adoption in this population (Hartley et al, 2010;Knudsen et al, 2010;Gopinath et al, 2011;Meyer & Hickson, 2012;Öberg et al, 2012;Meyer et al, 2014;Saunders et al, 2016;Pronk et al, 2017;Pronk et al, 2019;Sawyer et al, 2019;Sawyer et al, 2020). Furthermore, while previous research has similarly shown that hearing aid adoption and ownership is lower in older adults reporting better general health (Rosenhall & Espmark, 2003;Öberg et al, 2012;Meyer et al, 2014), our study further suggests that the presence of specific noncommunicable diseases, namely, hypertension and diabetes, are associated with lower odds of hearing aid adoption.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Overall, our findings in a large and recent clinical sample of older adults converge with the existent literature, showing self-reported hearing difficulties, audiometric hearing loss, and age are some of the strongest predictors of hearing aid adoption in this population (Hartley et al, 2010;Knudsen et al, 2010;Gopinath et al, 2011;Meyer & Hickson, 2012;Öberg et al, 2012;Meyer et al, 2014;Saunders et al, 2016;Pronk et al, 2017;Pronk et al, 2019;Sawyer et al, 2019;Sawyer et al, 2020). Furthermore, while previous research has similarly shown that hearing aid adoption and ownership is lower in older adults reporting better general health (Rosenhall & Espmark, 2003;Öberg et al, 2012;Meyer et al, 2014), our study further suggests that the presence of specific noncommunicable diseases, namely, hypertension and diabetes, are associated with lower odds of hearing aid adoption.…”
Section: Discussionsupporting
confidence: 85%
“…While the reviews completed by Knudsen et al (2010) and Meyer and Hickson (2012) spanned three decades of research (from 1980 to 2010), most of the studies included employed crosssectional study designs of small, clinic-based samples. Successive studies investigating the factors that predict hearing aid adoption and/or use have subsequently attempted to investigate much larger populations (Hartley et al, 2010;Gopinath et al, 2011;Öberg et al, 2012;Meyer et al, 2014;Saunders et al, 2016;Pronk et al, 2017;Pronk et al, 2019;Sawyer et al, 2019;Sawyer et al, 2020). For example, in a community-based sample of 1,371 older adults (>55 years) living in Australia, Gopinath et al (2011) found that, relative to non-owners, individuals that owned hearing aids were more likely to be older, self-report experiencing hearing loss and hearing handicap (or participation restrictions), and have poorer hearing sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence from the United Kingdom shows that specific demographic groups are unlikely to obtain hearing aids, proving that people of low SEP face other nonfinancial barriers. These differences do not only reflect the differences in the health systems and hearing aid provisions among countries, as suggested by Sawyer et al (2020), but also emphasize individuals' inability to identify their hearing difficulties as a barrier in their help-seeking process, even in countries where the hearing aids are available free of charge (Tsimpida et al, 2020a).…”
Section: Resultsmentioning
confidence: 99%
“…For example, two listeners with the same audiometric thresholds can have different speech-in-noise performance ( Gifford et al, 2007 ), and many individuals report significant hearing difficulties that are not reflected in hearing threshold measurement ( Füllgrabe et al, 2015 ; Bakay et al, 2018 ; Barbee et al, 2018 ; Vermiglio et al, 2018 ). In contrast, a large study exploring access barriers to hearing intervention in older adults, found that 40% of adults with audiometrically measurable hearing loss did not report a hearing difficulty ( Sawyer et al, 2020 ). The review findings indicate that, despite these well-evidenced shortcomings, measurement at the level of detection continues to be the dominant assessment measure reported in published studies of adults with hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…This information could be used in clinical practice and research to provide a more nuanced evaluation of the listening abilities of adults with hearing loss. The reductive approach to measurement described in this review may account for the contrast between what is measured and the priorities and perspectives of adults living with hearing loss ( Sawyer et al, 2020 ). The review findings may also assist in addressing the possible disconnect between people’s understanding of hearing loss and its relationship to communication.…”
Section: Discussionmentioning
confidence: 99%